Endogenous gamma interferon is essential in granuloma formation induced by glycolipid-containing mycolic acid in mice. - Asano, M (1993)
The present study examined the role of endogenous gamma interferon (IFN-gamma) in the formation of granulomas in mice which had been given a single intravenous injection of glycolipid-containing mycolic acid (trehalose 2,3,6'-trimycolate) purified from cell walls of Rhodococcus aurantiacus (Gordona aurantiaca) (GaGM) in the form of liposome. The histological status of granuloma formation in the livers, spleens, and lungs of GaGM-injected mice was studied at weeks 1 through 5, and the titers of endogenous IFN-gamma in all of these organ extracts and in the sera were determined by enzyme-linked immunosorbent assay. The granulomas, composed of epithelioid cells, developed until 3 weeks postinjection, and thereafter the granulomas regressed. The production of endogenous IFN-gamma was biphasic, with an early phase detected at days 1 through 3 and a late phase detected at weeks 1 through 5. The latter peak of endogenous IFN-gamma production proceeded in parallel with granuloma formation. Both the areas of granulomas and titers of IFN-gamma in these organs were dependent on the doses of GaGM used for injection. The cells which produce endogenous IFN-gamma in the spleens appear within the granulomas. To study the role of endogenous IFN-gamma in granuloma formation, the in vivo administration of rat anti-mouse IFN-gamma monoclonal antibody was carried out. Anti-mouse IFN-gamma monoclonal antibody neutralized endogenous IFN-gamma and resulted in the suppression of the number of granulomas and the size of each granuloma. These findings suggest that biphasic production of endogenous IFN-gamma in the local lesions may be crucial to the formation and development of the granulomas.